RIGIDITYOF NEWS ROUTINES AND SOCIAL MEANINGCONSTRUCTION IN NIGERIA: A REIMAGINATION - Amadi, Fred A. (European Scientific Journal, ESJ, 2015)
The search for the best model for journalism practice has inspired debates right from the ancient European era through to the era of the Penny Press in the formative years of the United States to the present. This paper is designed to explore what journalists understand by news routine as well as to explore the link between such understanding and journalists’ identification, description, expansion and dissemination of social meaning in Nigeria. In conformity with the notion that the representativeness of a sample to the general population is of no significance in qualitative research, a theoretical sample of three Nigerian newspaper texts were interpreted in accordance with analytic procedures prescribed in Semiotics and Critical Discourse Analysis. When Focus Group data were triangulated with the representation made with the newspaper texts, the finding was that Nigerian journalists legitimize the arbitrary by embracing rigid ideologically-tainted news routines. Conclusion is that such legitimization constitutes impediment to Nigeria’s development by undermining journalists’ capacity forcapacious construction and dissemination of social meaning.